2017
DOI: 10.22159/ijap.2017.v9s1.51_57
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Optimization and Virtual Screening Indonesian Herbal Database as Human Immunodeficiency Virus -1 Integrase Inhibitor Using Autodock and Vina

Abstract: Objective: Human immunodeficiency virus (HIV-1) is a virus that causes acquired immunodeficiency syndrome, a disease considered to be one of themost dangerous because of its high mortality, morbidity, and infectivity. The emergence of mutant HIV strains has led treatment to target proteaseas reverse transcriptase and integrase enzyme become less effective. This study aims to provide knowledge about the potential of HIV-1 integraseinhibitors for use as guiding compounds in the development of new anti-HIV drugs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Health and medical employees, especially physicians and dentists, are at two major risks regarding the infectious diseases. First, they are at a higher risk of infectious agents than other people, and they are considered as potential vector for transmission of infectious agents to their patients [10]. Among health personnel, dentists and their patients are always at a high risk of infections transmitted through blood due to blood-borne infections and other body fluids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Health and medical employees, especially physicians and dentists, are at two major risks regarding the infectious diseases. First, they are at a higher risk of infectious agents than other people, and they are considered as potential vector for transmission of infectious agents to their patients [10]. Among health personnel, dentists and their patients are always at a high risk of infections transmitted through blood due to blood-borne infections and other body fluids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual screening (VS) is a computational filter to reduce the size of a chemical library that will be identified experimentally and offers opportunities to quickly reduce the time and effort associated with identification 7 . VS is described as the use of high-performance computational calculations in analyzing a database of many chemical compounds in order to identify the probability of drug candidates 22 . There are two fundamental approaches to virtual screening: the ligand-based approach and the receptor-based approach.…”
Section: Resultsmentioning
confidence: 99%
“…The study reveals that IVM at a dose of 5 µM inhibits the replication of SARS-CoV-2 in vitro with an IC 50 of 2.2-2.8 µM, which is similar to the efficacy of IVM in dengue virus (IC 50 : 2.2µM for DENVI). Further, a single addition of IVM 2-h post-infection with SARS-CoV-2 was able to effect ≈5000 fold reduction in viral RNA at 48 h. At 24 th h, there was a 93% reduction in viral RNA and a 99.98% reduction at 48 th h. In an observational registrybased study [7] from 169 hospitals with 1970 COVID-19 patient's with lung injury requiring mechanical ventilation across Asia, Europe, Africa, North, and South America, the IVM, 150 mcg/kg treatment group (n=52) has lesser mortality rate, length of stay in intensive care unit and hospital compared to that of n=1918 conventionally treated patients (mortality rate=7.7% vs. 18.6%; hospital length of stay=10.9±6.1 days vs. 15.7±8.1 days, and intensive care unit length of stay=6.0±3.9 days vs. 8.2±6.2 days for IVM, and conventional treatment group resp, all at p<0.001 resp). This study was first of its kind for evaluating the significance of IVM in the treatment of COVID-19 in in vivo.…”
Section: Ivm and Sars-cov-2mentioning
confidence: 89%
“…Ivermectin (IVM), one such drug which is originally used to treat parasitic infections, has recently been found to inhibit the replication of novel SARS-CoV-2 within 48 h in laboratory settings [6]. The very recent observational registry-based study from 169 hospitals across different countries revealed that IVM treated group of COVID-19 critically ill patients requiring mechanical ventilation has lower mortality and healthcare resource used [7]. IVM is an Food and Drug Administration (FDA)-approved anti-parasitic drug that has also been shown to be effective in vitro against a broad range of viruses, including human immunodeficiency virus (HIV), dengue, and influenza [8,9].…”
Section: Introductionmentioning
confidence: 99%